Theoretical Study of the Stability of Acetylcholine Based on Molecular Orbital Theory using Density Functional Theory - Febriana, Fitri Noor; Khoirunisa, Vera; Mark-Lee, Wun Fui; Rusydi, Febdian (Universitas Airlangga, 2022)
Some molecules in nature have a positive or negative charge. One such molecule is acetylcholine. Acetylcholine is a positively charged molecule that is responsible for Alzheimer's disease. This study evaluated acetylcholine through six simple molecules based on the ionization potential and the HOMO-LUMO gap obtained from the density functional theory calculation. The calculation results showed that the ionization potential and the HOMO-LUMO gap could explain the stability of acetylcholine and the six other molecules. As a result, acetylcholine has the same properties as five other simple molecules. Meanwhile, one other molecule has the opposite properties to acetylcholine.